PANCASILA CONTENT CREATOR PROJECT DESIGN TO IMPROVE UNDERSTANDING OF PANCASILA VALUES - Encep Syarief Nurdin; Yadi Ruyadi; Tri Suhartati; eny supriyati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Understanding Pancasila values among the younger generation is crucial. The numerous cases of violence and bullying among the younger generation indicate that their character is not yet fully aligned with Pancasila values, necessitating an effective and creative development model. This study aims to develop a character development model for the younger generation through a Pancasila content creator project to enhance understanding of Pancasila values. This study uses a mixed-methods approach, namely qualitative and quantitative, with stages of analysis, exploration, and development of a character development model focused on Pancasila values. Data were collected through interviews, observations, questionnaires, and documentation studies, with subjects including training participants, training committee members, instructors, and officials at the Pancasila Ideology Development Agency. The research results show that: 1) Good training planning is key to success in improving understanding of Pancasila values. The process involves needs analysis and model design that focuses on project-based learning methods. Good planning can produce a model that is relevant, applicable, and able to encourage the interest of training participants and make it more interactive. 2) The implementation of the character development model for the younger generation through the Pancasila content creator project can be effectively applied to improve understanding and practice of Pancasila values among the younger generation. Therefore, character development through the Pancasila content creator project model is highly effective as a character development tool for the younger generation.